2022
DOI: 10.3390/jpm13010010
|View full text |Cite
|
Sign up to set email alerts
|

cMetS Based on Z-Scores as an Accurate and Efficient Scoring System to Determine Metabolic Syndrome in Spanish Adolescents

Abstract: The definition of metabolic syndrome (MetS) based on dichotomous cut-off points is efficient in the adult population. However, to date, there is no international consensus on how to define MetS in the pediatric population. For that reason, a continuous MetS score (cMetS) has been proposed for the pediatric population. However, despite multiple attempts, cMetS has not been fully validated as there is no agreement about the most accurate score to calculate it. The purpose of the present study was to compare the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…We agree that there is evidence indicating differences in glucose metabolism between sexes in people over 20 years of age. However, we have previously conducted extensive work on large groups of adolescents of the same age as the participants in the present study (12-16 years) and found no such differences in glucose, insulin, and HOMA-IR values between boys and girls [13,60]. It is also possible that glucose levels and HOMA-IR values were higher if they had been measured in plasma, but that would have affected both obese and normal-weight groups.…”
Section: Discussionmentioning
confidence: 52%
“…We agree that there is evidence indicating differences in glucose metabolism between sexes in people over 20 years of age. However, we have previously conducted extensive work on large groups of adolescents of the same age as the participants in the present study (12-16 years) and found no such differences in glucose, insulin, and HOMA-IR values between boys and girls [13,60]. It is also possible that glucose levels and HOMA-IR values were higher if they had been measured in plasma, but that would have affected both obese and normal-weight groups.…”
Section: Discussionmentioning
confidence: 52%
“…Several authors have used a cMetS to avoid potential misclassification [ 25 28 ]. According to Fernandez-Aparicio [ 29 ], cardiometabolic risk score based on the z-score is an accurate and efficient method that can be used to determine MetS risk in adolescents. Indeed, a recent meta-analysis [ 30 ] reported a pooled sensitivity and a specificity of cMetS risk scores in predicting the risk of MetS: 0.90 (95% confidence interval (CI), 0.83–0.95) and 0.86 (95% CI, 0.83–0.89), respectively.…”
Section: Discussionmentioning
confidence: 99%